Kombinasi Terapi Reminisence Dan Relaksasi Otot Progresif Menurunkan Depresi Pada Lansia Dengan Hipertensi - Tobing, Duma Lumban; Novianti, Evin (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Hypertension is a health problem that is often found in the elderly group. Hypertension can havepsychological effects such as depression. Reminiscence therapy and progressive muscle relaxation areforms of psychotherapy that can be used to reduce symptoms of depression. This study aims to determinethe effectiveness of a combination of reminiscence therapy and progressive muscle relaxation on the levelof depression in elderly people with hypertension. The research design used was quasi-experimental withpre-test and post-test with a control group. The study respondents were 26 elderly divided into interventionand control groups. The sampling technique used was purposive sampling. The level of depression wasmeasured using the Geriatric Depression Scale instrument. Data were analyzed using the Wilcoxon test tosee before-after differences in the intervention group and the control group. Mann-Whitney analysis wasused to determine the effect of therapy between the intervention group and the control group after theintervention. The results showed that the value of p = 0.001 (p <0.05), which means that the combination ofreminiscence therapy and progressive muscle relaxation therapy can significantly reduce the level ofdepression in the elderly with hypertension. The combination of reminiscence therapy and progressivemuscle relaxation is useful for reducing depression in the elderly and is recommended as a nursing therapy